Must We Be Courageous? - Hamric, Ann B. (The Hastings Center report, 2015)
The notion of virtue in general, and courage in particular, has had a hard time integrating itself into the everyday lexicon of bioethics. Following the lead of enlightenment moral philosophy, which concentrates on the theory of right action as opposed to the ancient Greeks' emphasis on the development of good character, bioethics, with some notable exceptions, has tended to relegate consideration of the virtues to the sidelines of moral argument. Recently, however, there have been calls for the necessity of “moral courage” in the context of clinical ethics. As nurses, physicians, and other health care professionals confront a variety of moral contexts in which the virtue of courage is invoked to 'do the right thing,' stand up for patients' rights, and uphold the ethical standards of their professions, they are increasingly reminded of their moral duty to exhibit courage in the face of institutional obstacles to the proper care of their patients. For example, a nurse's hesitation to approach a physician to request increased sedation for an agitated patient out of fear of retaliation is represented in one article as a lack of courage. In this paper we offer a critical assessment of such invocations of courage. While we find courage to be an indispensable virtue in some challenging contexts, in other settings we find invocations of courage to be both an unfortunate endorsement of an oppressive status quo that can divert attention from the real problems and an undesirable and potentially destructive strategy within health care institutions whose goal is medically excellent and morally good clinical practice. As we shall argue, a call to virtuousness is not always virtuous.